The genetic structures of the Churu, Ede and Giarai unravelled by complete mitochondrial DNA - Dinh, Huong Thao; Tran, Huu Dinh; Nguyen, Thuy Duong (Academia Journal of Biology, 2024)
Vietnam, a nation with a rich and complex history of migration and settlement, is home to 5 fundamental language families: Austroasiatic (AA), Tai-Kadai (TK), Austronesian (AN), Sino-Tibetan (ST) and Hmong-Mien (HM). Among them is the Austronesian, a language family substantial in island Southeast Asia (ISEA) but marginal in mainland counterpart (MSEA), constituted five Vietnamese ethnolinguistic groups. Here, we analyzed the control region, and the complete mitochondrial DNA (mtDNA) of 121 individuals from 3 AN-speaking populations (Churu, Ede, and Giarai). To explore the molecular diversity, the sequences were aligned against the Reconstructed Sapiens Reference Sequence (RSRS). The quantification and distribution of nucleotide variations resulted in 6,369 variants in our dataset in which the control region and coding region retained 1,707 and 4,662 variants, respectively. Churu harbored the most diversity (54.6 ± 2.8 variants/person), followed by Giarai (52.2 ± 3.3 variants/person), and Ede (51.1 ± 5.3 variants/person). Both the control region and whole mtDNA were input to Haplogrep3 to call haplogroups, resulting in 47.11% of our samples having their haplogroup changed from 17 whole mtDNA lineages to 16 different control region lineages. The haplogroup profile derived from whole mtDNA included 31 unique clades, in which only B5a1d was shared among three groups, and 23/31 lineages were present exclusively in a single population. The haplogroup component of each minority also revealed that all 3 AN groups had the majority of their samples attributed to the macrohaplogroups M, B, and F, with the disparity fixed in their underlying sublineages. This study increased the knowledge wealth of the genetic characteristics of AN speakers in the region from a different analysis approach, and highlighted the contribution of variants in different complete mtDNA, providing insight to reconstruct a comprehensive genetic architecture of Vietnam.